USING GAMES AS AN EFFICIENT WAY OF TEACHING VOCABULARY - Allanyazov Marat Baxavedinovich (American Journals Publishing, 2023)
The following article defines significance of using games in teaching vocabulary for ESL learners. One of the most effective activities that support the students’ vocabulary are games. Games can help and encourage many learners to learn target language more easily.
Keywords: target words, game-based learning, appropriate teaching strategy, time-fillers.